The Membrane Interaction of Alpha-Synuclein - Liu, Cencen; Zhao, Yunfei; Xi, Huan; Jiang, Jie; Yu, Yang; Dong, Wei (Frontiers in Cellular Neuroscience, 2021)
A presynaptic protein closely related to Parkinson’s disease (PD), α-synuclein (α-Syn) has been studied extensively regarding its pathogenic mechanisms. As a physiological protein in presynapses, however, α-Syn’s physiological function remains unclear. Its location in nerve terminals and effect on membrane fusion also imply its functional role in synaptic transmission, including its possible interaction with high-curvature membranes via its N-terminus and amorphous C-terminus. PD-related mutants that disrupt the membrane interaction (e.g., A30P and G51D) additionally suggest a relationship between α-Syn’s pathogenic mechanisms and physiological roles through the membrane binding. Here, we summarize recent research on how α-Syn and its variants interact with membranes and influence synaptic transmission. We list several membrane-related connections between the protein’s physiological function and pathological mechanisms that stand to expand current understandings of α-Syn.